Association of serum fetuin A with mineral bone disorders in patients undergoing high flux hemodialysis versus hemodiafiltration - Mohammed Younus Naji Al Atbee; Hala Sami Tuama; Rafid Abdulwahid Gatee (YCAB Publisher, 2026)
Background: Chronic kidney disease (CKD) is a growing worldwide health issue, and end-stage renal disease (ESRD) patients typically need RRT to survive. Hemodialysis (HD) and Hemodiafiltration (HDF) are popular RRT modalities. Waste removal, electrolyte balance, and MBD management in ESRD patients are the goals of these therapies. MBD, characterized by impaired bone metabolism, mineral homeostasis, and vascular calcification, is common and dangerous in this group. Fetuin A, a glycoprotein involved in MBD, has received interest recently. Serum fetuin A and mineral bone problems in high-flow hemodialysis patients compared to hemodiafiltration are reviewed in this research. Objectives: This study aims to analyze the association of serum fetuin A with mineral bone complaints in dialysis patients on high flux hemodialysis in associate with hemodiafiltration. Method: cases collected from Basrah Teaching Hospital from October 2022 to October 2023. Written informed consent was obtained from all the patients who participated in the study. This study included 200 patients within the age range of 20-70 years with end stage kidney disease. Results: significant decrease in Fetuin (1672.3± 563.2. P-value =0.002), CRP (13.88±12.4 mm/hr. P-value =0.0001) in patients under HDF than patients under HD, significant increase in period of dialysis in group patients under HDF than patients in group HD, there is significant (P-value =0.04) positive correlation coefficients between fetuin and C-reactive protein (CRP). Conclusion: HDF may offer better bone disorder management and reduced inflammation than high flux HD. While HDF patients underwent longer dialysis, age and mineral metabolism markers were consistent across groups. The distinct relationship between fetuin A and CRP in HD underscores the complexity of these factors. Keywords: serum fetuin; mineral bone; disorders; dialysis; hemodialysis; hemodiafiltration